Switching speed improvements in multiphase buck converter via two-shunt voltage-sources - A. F. Yahaya, Jabbar; Mansor, Muhamad (TEXTROAD Publishing Corporation, 2017)
Multiphase Buck converters are well known for their smaller ripple current, smaller filter design and smaller component ratings. The converter operating responses however depend on the value of inductor and load resistance. Increasing the switching frequency can improve the transient responses. However, it reduces the system efficiency and controlling the current response can be complex. This paper proposes an improved multiphase buck converter for a lithium-ion battery charging applications. The proposed system is based on the ‘Bi-level drives’ concept, which requires two input voltage in which one is higher than the other input and is connected in series to the system. By driving the load with a higher input voltage, the transient response is observed to be much faster. Upon reaching the desired reference output, the system will revert to a lower input voltage, thus, the efficiency of the system will not be affected. This scheme requires additional two power switches and a power diode. The operation and the switching scheme will be discussed in this paper.